Menari Bersama Hegel di Era Post-Truth: Dialektika, Moralitas, dan Pengembangan Karakter - Julius Stefanus Sibagariang (Bina Nusantara University, 2026)
The post-truth era is characterized by the weakening of the authority of truth, the dominance of emotion over rationality, and the fragmentation of the public sphere, which has led to a moral crisis and the fragility of human character. This study aims to explore the relevance of Hegel's philosophy as a conceptual framework for responding to this crisis. Using a qualitative method based on literature studies and Hegel's dialectical analysis, this study reinterprets the concepts of ‘Geist’, ‘Bildung’, and ‘Sittlichkeit’ as strategies for character development. The results of the study show that true character can only be formed through intersubjective consciousness, historical-cultural processes, and ethical praxis in the community. Therefore, character education in the post-truth era should not stop at digital literacy or the internalization of moral values, but must foster critical reflection, moral courage, and active participation in ethical life together. This study concludes that the post-truth crisis is not only a threat, but also a dialectical opportunity to strengthen human integrity and rebuild the moral foundations of contemporary society.